2020
DOI: 10.1097/eja.0000000000001265
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative atrial fibrillation following emergency noncardiothoracic surgery

Abstract: BACKGROUND Postoperative atrial fibrillation (POAF) occurs frequently following cardiothoracic surgery and is associated with a higher mortality and a longer hospital stay. The condition is less studied following noncardiothoracic surgery as well as emergency surgery. OBJECTIVE The aim of this systematic review was to investigate the occurrence of atrial fibrillation following emergency noncardiothoracic surgery and associated risk factors and mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…There is one exception, the Reporting subscale, which scored 0 to 2. In accordance with previous systematic reviews [ 26 , 27 ], it was decided to modify the original Power item (dealing with sufficient statistical power) as the question was deemed unclear and could not be adequately resolved. This item was simplified to a score of 0 (no sample size calculation) or 1 (sample size calculation reported).…”
Section: Methodsmentioning
confidence: 99%
“…There is one exception, the Reporting subscale, which scored 0 to 2. In accordance with previous systematic reviews [ 26 , 27 ], it was decided to modify the original Power item (dealing with sufficient statistical power) as the question was deemed unclear and could not be adequately resolved. This item was simplified to a score of 0 (no sample size calculation) or 1 (sample size calculation reported).…”
Section: Methodsmentioning
confidence: 99%
“…The peak incidence occurred 1–3 d post-surgery, ranging from 0.37% in large population studies of non-cardiothoracic surgery to 30% after major non-cardiothoracic surgery, such as pneumonectomy. 17 , 18 , 19 Mcfalls et al. 20 reported that coronary revascularization before elective macrovascular surgery did not improve long-term survival or reduce the incidence of early postoperative outcomes, including death, MI, and length of hospital stay in patients with stable CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have associated the occurrence of POAF after pulmonary resection is related to various patient factors, including age, extent of lung tissue resection, gender, clinical stage, history of coronary heart disease, and mediastinal lymph node dissection [1,[3][4][5][6][7][8][9] , but the exact causative relationship remains unclear. Advancements in lung cancer surgery, including VATS and lung-sparing procedures, have changed the landscape, requiring a reevaluation of risk factors.…”
Section: Introductionmentioning
confidence: 99%